Kotributor Kinerja Industri : Modal, Pengetahuan dan Inovasi - Ahmad, Upi Sopiah (Lembaga Yasin AlSys, 2023)
From time to time the development of science is increasingly advanced and high, so that entrepreneurs are required to produce a product or goods that they produce in order to have more selling value. Therefore entrepreneurs must have sufficient capital, extensive knowledge and always innovate is a demand. Capital, entrepreneurial knowledge and innovation are interrelated and related to each other so that they will be able to improve industry performance. Capital that must be prepared by a beginner in doing business, namely, experience, knowledge, skill, courage and equity. Business owners must have sufficient knowledge, especially knowledge in managing a business that we run, business owners must have a personality that is responsible for leading employees who work where they carry out a business. Lack of creativity and innovation can affect a business performance. Because creativity connects and rearranges knowledge in the minds of humans who allow themselves to think more freely in generating new things or generating ideas that surprise others in producing something useful and always innovating in improving the quality of the products produced. , regardless of the desire of consumers who want to get quality goods in a good and attractive way. In the Islamic economic system, capital must continue to grow, meaning that capital must rotate so that the business being carried out continues to grow. The importance of capital in human life is addressed in the Al-Qur'an letter Al-Imran Verse 14: and in the verses of the Al-Qur'an letter at-taha verse 114 it is stated about knowledge, while performance in Islam is an ordinance or procedure in accordance with established standards. set.